TINJAUAN KRIMINOLOGIS PENJUALAN OBAT KERAS GOLONGAN G TANPA MEMENUHI PERSYARATAN KEAMANAN DI KABUPATEN TIMOR TENGAH SELATAN - Leni, Maldo Jupiter; Manafe, Deddy R. CH; Dima, Adrianus Djara (The Juris, 2025)
The sale of hard drugs classified as Group G without meeting safety requirements has become a serious issue in Indonesia due to the high risk of misuse and the threat it poses to public health. In Timor Tengah Selatan Regency, several small kiosks have been found illegally selling these drugs without proper licenses and oversight. Commonly sold drugs include Mefenamic Acid, Amoxicillin Trihydrate, Piroxicam, Dexaharsen, and Antalgin. The main motive of the perpetrators is financial gain. This research to identify the factors that contribute to the sale of Class G prescription drugs without meeting safety requirements in Timor Tengah Selatan Regency, to examine the efforts made to address and mitigate the sale of Class G prescription drugs that not comply with safety regulations in Timor Tengah Selatan Regency. This research is empirical research with a legal sociological approach method that it is based on data obtained in the field through interviews with 8 respondents. The data collection techniques used in this study: observation, interviews, and literature review. Results study indicate that the factors contributing to the sale of Class G prescription drugs without meeting safety requirements in Timor Tengah Selatan Regency include a lack of legal awareness, economic motives (profit-seeking), and environmental factors specifically, unequal infrastructure development and the demands of the local community; efforts to address the sale of these drugs involve both preventive and repressive measures carried out by the Timor Tengah Selatan Resort Police.